2015
DOI: 10.3892/ol.2015.3541
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-195 inhibits the proliferation, migration and invasion of cervical cancer cells via the inhibition of CCND2 and MYB expression

Abstract: Abstract. The functions of microRNAs (miRNA/miR) in the development of cervical cancer remain largely undefined. The present study investigated the role of miR-195 in cervical cancer development. The expression of miR-195 mimics in the cervical cancer HeLa cell line significantly decreased the cell proliferation, migration and invasion capacities in vitro. Using miRNA target prediction algorithms and reporter assays, cyclin D2 (CCND2) and v-myb avian myeloblastosis viral oncogene homolog (MYB) were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
(27 reference statements)
3
23
0
Order By: Relevance
“…miRNA has previously been identified as an important factor in cell proliferation, division, metastasis or apoptosis in cervical cancer (20). In the present study, it was demonstrated that miR-10-5p was significantly downregulated in cervical cancer compared with normal cervical cells.…”
Section: Discussionsupporting
confidence: 61%
“…miRNA has previously been identified as an important factor in cell proliferation, division, metastasis or apoptosis in cervical cancer (20). In the present study, it was demonstrated that miR-10-5p was significantly downregulated in cervical cancer compared with normal cervical cells.…”
Section: Discussionsupporting
confidence: 61%
“…The function of miR-195 in CC has been widely probed, and it is certified that miR-195 inhibits CC cell proliferation, invasion and migration by targeting related genes, while the knockdown of miR-195 has the opposite impact on cell processes [3,6,24,25]. In this study, we further demonstrated that miR-195-5p could lessen CC cell proliferation and invasion ability via targeting MMP14.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 49%
“…Cervical carcinoma (CC) is the third most prevalent cancer and the fourth mortality leading cancer in females worldwide, for which the treatment remains a problem [3]. The aim of the present study was to find new biomarkers and hereby improve the current therapy methods for CC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations